2001
DOI: 10.1053/rmed.2001.1174
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation and structural changes in the airways of patients with primary Sjögren's syndrome

Abstract: The present study aimed to compare the cellular pattern and structural changes in the airways of patients with primary Sjögren's syndrome (pSS) with healthy controls. Bronchial biopsy specimens were obtained from seven subjects with pSS and seven healthy controls. All the patients with pSS had increased bronchial responsiveness to methacholine. In the biopsies inflammatory cells, cytokine-producing cells, tenascin and laminin were visual zed by immunostaining. Patients with pSS had a higher number of neutrophi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 20 publications
2
19
0
1
Order By: Relevance
“…Previously, studies have shown that increased TN-C levels are observed in multiple autoimmune diseases (Midwood et al, 2009), including rheumatoid arthritis, Sjogren's syndrome (Amin et al, 2001), and diabetes (Loots et al, 1998). Our data shows that exogenous TN-C, together with oxLDL (5 μg/ml) is capable of activating foam cell formation.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Previously, studies have shown that increased TN-C levels are observed in multiple autoimmune diseases (Midwood et al, 2009), including rheumatoid arthritis, Sjogren's syndrome (Amin et al, 2001), and diabetes (Loots et al, 1998). Our data shows that exogenous TN-C, together with oxLDL (5 μg/ml) is capable of activating foam cell formation.…”
Section: Discussionsupporting
confidence: 60%
“…It is not normally expressed in most adult tissues but is specifically and transiently upregulated during acute inflammation and persistently expressed in chronic inflammation (Chiquet-Ehrismann and Chiquet, 2003). Previous studies have shown that increased TN-C levels are observed in multiple autoimmune diseases (Midwood et al, 2009), including rheumatoid arthritis, Sjogren's syndrome (Amin et al, 2001), and diabetes (Loots et al, 1998). However, the potential function of TN-C in foam cell formation and atherosclerosis was barely understood.…”
Section: Discussionmentioning
confidence: 99%
“…10 patients had infiltration of bronchi and bronchiole submucosa by lymphocytes, which were CD4+T-lymphocytes in six patients [56]. Another study described neutrophils and mast cells in the bronchi of patients with primary Sjö gren's syndrome [57]. Finally, a Japanese study found no difference in cells infiltrating small airways between primary and secondary Sjö gren's syndromes [58].…”
Section: Connective Tissue Diseasesmentioning
confidence: 97%
“…Furthermore, multifocal cysts were seen in six of 51 patients (two with LIP, two with malignant lymphoma, two with amyloidosis). Some authors have proposed that the formation of bronchioectasis and cystic changes might be due to air-trapping occurring as the result of chronic bronchial inflammation and increased epithelial airway damage by inflammatory cells (20,21). We suggest that some SS patients with multiple cysts in chest CT were complicated with LIP, malignant lymphoma, and amyloidosis (4,18).…”
Section: Discussionmentioning
confidence: 77%